Intersectionality: Understanding the Interdependent Systems of Discrimination and Disadvantage - King-Mullins, Erin; Maccou, Elana; Miller, Pringl (Clinics in Colon and Rectal Surgery, 2023)
The fight for gender equity in surgery extends well beyond the simplistic binary construct of man versus woman. Professor Kimberlé Crenshaw coined the term “intersectionality,” which is used to describe the dynamic associations between the concepts of race, class, gender, and other individualized characteristics and their real-time interaction with one another in our society. Our review of intersectional identities among medical professionals attempts to examine the trends of difficulties at the intersections of an individual's identity within academic surgery, leadership in academic surgery, and the effects on patient outcomes in the United States. Specifically, we will focus on the interaction of race, ethnicity, religion, sexual orientation, family, disability, and international status. Much more research focused specifically on intersectional groups is required to statistically identify to what degree overlapping identities impact professional and patient care outcomes. Recognition of the problem and candid discussions will allow for vast improvements not only in surgical culture, but also in surgical care.
Keywords: diversity; intersectionality; LGBTQ; women in surgery